ANALISA VALUE CREATION PADA PERGURUAN TINGGI SWASTA DI SURABAYA BERDASARKAN PERSEPSI MAHASISWA JURUSAN MANAJEMEN - Cynthia Poco (Business Accounting Review, 2013)
The Competition in Indonesia’s University becomes tougher especially in Private Universities. Private Universities also must be able to create student value to persist in tight competition. Value Creation only happens when the students get benefits more than price that they paid. Therefore, measuring value creation must be done by the Universities. The data were collected by means of distributing questionnaires to the active students in five universities of management department of 2009, 2010 or 2011 that have the GPA value between 2.00 to 4,00. Data analysis used in this research was One Way Anova test through software SPSS 20 for Windows. Based on Analysis of Variance, it was concluded that there was no significant difference in universities value creation based on gender, however it was found that there was significant different in value creation based on the students GPA and seniority.